Healthcare utilization by children with neurological impairments and disabilities in rural Kenya: a retrospective cohort study combined with secondary analysis of audit data - Abuga, J; Mwangi, L; Ndolo, J; Kariuki, S; Newton, C (F1000Research, 2022)
Background: There is a paucity of data on healthcare utilization by children with neurological impairments (NI) in sub-Saharan Africa. We determined the rate, risk factors, causes, and outcomes of hospital admission and utilization patterns for rehabilitative care among children with NI in a defined rural area in Kenya. Methods: We designed two sub-studies to address the primary objectives. Firstly, we retrospectively observed 251 children aged 6–9 years with NI and 2162 age-matched controls to determine the rate, causes and outcomes of hospitalization in a local referral hospital. The two cohorts were identified from an epidemiological survey conducted in 2015 in a defined geographical area. Secondly, we reviewed hospital records to characterize utilization patterns for rehabilitative care. Results: Thirty-four in-patient admissions occurred in 8503 person-years of observation (PYO), yielding a crude rate of 400 admissions per 100 000 PYO (95% confidence interval (Cl): 286–560). The risk of admission was similar between cases and controls (rate ratio=0.70, 95%CI: 0.10–2.30, p = 0.31). The presence of electricity in the household was associated with reduced odds of admission (odds ratio=0.32, 95% Cl: 0.10–0.90, p < 0.01). Seizures and malaria were the main causes of admission. We confirmed six (0.3%) deaths during the follow-up period. Over 93% of outpatient paediatric visits for rehabilitative care were related to cerebral palsy and intellectual developmental delay. Health education (87%), rehabilitative exercises (79%) and assistive technology (64%) were the most common interventions. Conclusions: Surprisingly, the risk of hospitalization was not different between children with NI and those without, possibly because those with severe NI who died before this follow-up were under seclusion and restraint in the community. Evidence-based and tailored rehabilitative interventions are urgently required based on the existing secondary data.